Different types of screen time and its effect towards social and emotional development among preschoolers in Labuan / Padma A Rahman and Maznina Azureen - A Rahman, Padma; Azureen, Maznina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Over recent years, there are growing literatures associating screen time with physical and psychological adverse consequences. Excessive and regular exposure to electronic device had shown to influence brain development, affecting language and social competences. This study investigated different types of screen time and its effect on social and emotional development among pre-schooler in Labuan. This was a cross-sectional self-report survey with 143 parents with child aged between 4 to 6 years old. The Strengths and Difficulties Questionnaire (SDQ) was used in identifying emotional and behavioural problems among these children. Descriptive statistics were calculated, and associations were examined using the Fisher FreemanHalton Test. Results indicated that the majority (51%) of the pre-schoolers were exposed to screen time through the use of smartphones. Most or 43.5% spend an average of 2 to 3 hours on-screen during weekdays and it was found that screen time among pre-schoolers was increased during the weekend. There is no significant relationship found between parents’ demographic characteristics and screen time exposure among preschoolers (p> 0.05) and no association was found between a child’s demographic profiles with social and emotional development (p>0.05). However, the study showed that there is a significant association between average screen time spend during weekdays with social and emotional development (p= 0.021). In conclusion, different types of screen time did not affect the social and emotional development among preschoolers, but excessive usage may still have the tendency to affect negatively. Future study should better account for the methodological limitations of the extant studies to seek to understand the prolonged effects of excessive screen-times among preschoolers.